The impact of GNSS antenna mounting during absolute field calibration on phase center correction – JAV_GRANT-G3T antenna case study - Dawidowicz, Karol; Krzan, Grzegorz; Baryła, Radosław; Świątek, Krzysztof (International Conference “Environmental Engineering”, 2017)
The phase center corrections (PCC) of an GNSS antenna can be precisely determined using the absolute field calibration procedure with a precise robot. Using the Hannover’s automated absolute antenna field calibration technique developed by the Institute of Geodesy (University of Hannover) and Geo++ we demonstrate that the way of antenna mounting on the robot (distance from mechanical structures mounted underneath the antennas) can cause significant changes in the phase center offset and variations. For both the GPS and the GLONASS carrier signals L1 and L2 these changes are in the order of several millimeters. e also analyzed how these changes transfer to the coordinate domain. We investigated the differences between position estimates obtained using two different, individual and type-mean, elevation dependent PCC. There days of GNSS observations on very short baseline were used for these studies. The position time-series were derived using the RTKLib software package. We found that that the differences in the calibrations models propagate directly into the position domain, affecting sub-daily results and giving visible periodic variations in solutions. The best agreement with the “true position” we obtained using PCC from the individual calibrations.